2018
DOI: 10.4103/jlp.jlp_93_17
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern of Shigella isolates in a tertiary healthcare center

Abstract: BACKGROUND AND OBJECTIVES: Shigellosis is one of the most common causes of morbidity and mortality in children in developing countries. To the best of our knowledge, there is no published data in the study area on the antimicrobial susceptibility pattern and prevalence of Shigella species among diarrheagenic cases. Therefore, a retrospective analysis was done to find the Shigella serotypes, common age group affected, and antimicrobial resistance pattern of Shigella isolates in South Kerala METHODS: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Several studies across the world have also shown the increased resistance of Shigella species to third-generation cephalosporins (Radice et al, 2001;Vinh et al, 2009;Mandal et al, 2010). More recent research also consistently supports the fact that third-generation cephalosporins cannot be relied on treating Ciprofloxacin resistant Shigella species due to surge in third-generation cephalosporin-resistant Shigella species (Hosseini Nave et al, 2016;Nüesch-Inderbinen et al, 2016;Madhavan et al 2018;Abbasi et al, 2019;Bian et al, 2019). Therefore, although our study has shown the high susceptibility of Shigella species to a third-generation cephalosporin (Cefotaxime), we still suggest using thirdgeneration cephalosporin with caution.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several studies across the world have also shown the increased resistance of Shigella species to third-generation cephalosporins (Radice et al, 2001;Vinh et al, 2009;Mandal et al, 2010). More recent research also consistently supports the fact that third-generation cephalosporins cannot be relied on treating Ciprofloxacin resistant Shigella species due to surge in third-generation cephalosporin-resistant Shigella species (Hosseini Nave et al, 2016;Nüesch-Inderbinen et al, 2016;Madhavan et al 2018;Abbasi et al, 2019;Bian et al, 2019). Therefore, although our study has shown the high susceptibility of Shigella species to a third-generation cephalosporin (Cefotaxime), we still suggest using thirdgeneration cephalosporin with caution.…”
Section: Discussionmentioning
confidence: 89%
“…The high resistance level in Shigella can be attributed to the transfer of resistant determinants such as plasmids, integrons and transposons (Barrantes & Achí, 2016). Due to the rise in resistance to thirdgeneration cephalosporins (Abbasi et al, 2019), a recent study has suggested using Azithromycin and Piperacillin tazobactam as an alternative (Madhavan et al, 2018). However, resistance to Azithromycin has also been reported (Nüesch-Inderbinen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Shigella flexneri (21%) isolates from Iran were found to show resistance to cotrimoxazole (100%), ampicillin (100%), tetracycline (75%), chloramphenicol (50%), cefixime (50%), and ampicillin (33.30%) (Abbasi et al, 2019). A study from Kerala, India reported Shigella flexneri isolates to display resistance to nalidixic acid (88.80%), ampicillin (83.30%), cotrimoxazole (83.30%), ciprofloxacin (77.70%), and furazolidone (38.80%) (Madhavan et al, 2018). The Oceanic region of Australia had also reported ampicillin (77%), tetracycline (74%), chloramphenicol (60%), and sulfamethoxazole/trimethoprim (49%) resistant Shigella flexneri (Malau et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in North India showed that nearly 20% of S. flexneri were resistant to third generation cephalosporin by disc diffusion and 33.7% had MIC ≥1 μg/mL ( 31 ). Another study conducted in India showed that 91.6% of the Shigella isolates were multi drug resistant and presence of ESBL (Extended spectrum betalactamase) was detected in five isolates ( 32 ). Our patient who had MDR Shigella in stool was a 21 year old female, who was successfully managed with cotrimoxazole and other supportive measures.…”
Section: Discussionmentioning
confidence: 99%